BIOETIK: MANFAAT DAN TANTANAN BAGI ETIKA KRISTIANI - John Jeramu (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2017)
Currently science is found in a paradoxical situation: the basis of scientific activity and the interrelations between science, technology, industry, society and State are strongly questioned and criticized, at the same time that the worldly idea of science as the only motor for human development prevails. There is where the idea of bioethics arises as trans-disciplinary knowledge –for, to and from life- as another way of doing and producing knowledge. This article will explain about the relationship between bioethics and Christian ethics. In particular way, to see the impact and contribution of bioethics for Christian ethics. Dialogue of both is so necessary to respond the challenges of the accelerate progress of biomedicine and biotechnology, and in the same time, to put the ethics limits for technological progress in our times today. It is the way to reach a science and technology development that more responsibility, while respecting for human life and dignity. The fundamental question to be answered through this article is whether the bioethics is a problem or a solution for the human ethics today?